(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This paper analyzes the conception of citizenship, both in antiquity and modernity, ending with notes on the conception of citizenship in the Federal Constitution of Brazil (1988), highlighting, in each section, its main aspects in historical and analytical terms, for purposes of academic-scientific contribution to the general studies on citizenship, both in general terms and in specific Brazilian constitutional terms.